Prevenção e promoção de saúde no contexto escolar: formação continuada de professores em desenvolvimento de competências socioemocionais - Justo, Alice Reuwsaat (Universidade do Vale do Rio dos Sinos, 2019)
Socioemotional competence has been developed in school settings as a prevention and health promotion strategy. Literature shows the importance of teachers’ socioemotional competence for them and their students’ wellbeing and life quality. The present dissertation proposes an adaptation of Dialectical Behavioral Therapy Skills Training as a teachers’ continuing education intended to develop socioemotional competence. The study I investigate the relation between emotion regulation and educative social skills and measure 69 primary school teachers’ socioemotional competence. Evaluation of intervention effects, described at Study II, measure its effect at 27 teachers’ socioemotional competence at three periods and program feasibility per a mixed method study. It was found a little positive effect on quantitative analyses and optimal results from program feasibility, leading to conclude the necessity to extend intervention length. In Study III it is investigated the contributions of this approach to school settings through an experience report. It is concluded that Dialectical Behavioral Therapy can contribute to teachers achieve the specifics classrooms dialectical balance and presents a potential to attain complex and multifaceted issues present in school settings.
Keywords: Promoção de saúde; Competências socioemocionais; Terapia comportamental dialética; Formação continuada de professores; Health promotion; Socioemotional competence; Dialectical behavioral therapy; Teachers’ continuing education; ACCNPQ::Ciências Humanas::Psicologia